Gen pro FTO a jeho role v genetické determinaci obezity - Dlouhá, D; Hubáček, J A (Vnitrni lekarstvi, 2012)
Obesity is a risk factor for development of cardiovascular disease, type 2 diabetes and some cancers. Substantial proportions of obese people die from diseases caused by complications of overweight. The incidence of obesity in different populations exceeds 15%. The emergence of obesity is influenced by external factors (especially excessive energy intake and reduced physical activity). Body Mass Index (BMI) is also influenced by genetic factors, estimates of the degree of inheritance of obesity, according to the type of study range from 30 to 70%. Newly detected genetic risk factor for body weight is the FTO gene ("fat mass and obesity associated"). Variants in the first (and in some populations also in the third) intron of this gene are associated with BMI values and the presence of one risk allele is associated with an increase of body weight by about 1.5-2 kg. Studies on the possible causality (impact on energy intake, basal metabolism, physical activity) did not show consistent results. Variants in the first intron are also associated with higher risk of type 2 diabetes, polycystic ovary syndrome, and cardiovascular disease and seem to play a role in the determination of certain types of cancer and are associated with higher mortality. The exact mechanism of the effect of FTO on BMI determination is not yet known, however, the FTO exhibit a DNA demethylase activity and its role is designed as a transcription coactivator.
Keywords: Body Mass Index; bazální metabolismus; genetická predispozice k nemoci; gen pro FTO; Female; Humans; Basal Metabolism; Genetic Predisposition to Disease; lidé; ženské pohlaví; proteiny; nádory; obezita; Obesity; Polycystic Ovary Syndrome; kardiovaskulární nemoci; syndrom polycystických ovarií; Diabetes Mellitus, Type 2; Animals; Polymorphism, Genetic; zvířata; mutace; Neoplasms; Mutation; Proteins; polymorfismus genetický; index tělesné hmotnosti; diabetes mellitus 2. typu; Cardiovascular Diseases; Alpha-Ketoglutarate-Dependent Dioxygenase FTO